2009
DOI: 10.1016/j.jaci.2009.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Does higher body mass index contribute to worse asthma control in an urban population?

Abstract: Background-Epidemiologic findings support a positive association between asthma and obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
2
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 36 publications
0
35
2
4
Order By: Relevance
“…On the other hand, Clerisme-Beaty et al 21 performed a cross sectional assessment of asthma control in 292 patients with asthma. The majority were women (82%) and African-American (63%), recruited from primary care using 4 different validated survey tools: the Asthma Control and Communication Instrument, the Asthma Control Test, the ACQ, and the Asthma Therapy Assessment Questionnaire.…”
Section: Obesity and Asthma Controlmentioning
confidence: 99%
“…On the other hand, Clerisme-Beaty et al 21 performed a cross sectional assessment of asthma control in 292 patients with asthma. The majority were women (82%) and African-American (63%), recruited from primary care using 4 different validated survey tools: the Asthma Control and Communication Instrument, the Asthma Control Test, the ACQ, and the Asthma Therapy Assessment Questionnaire.…”
Section: Obesity and Asthma Controlmentioning
confidence: 99%
“…However, there are contradictory results in both adult and childhood researches about the association of obesity with severity of asthma (2)(3)(4)(5)(6). Some report that obesity increases asthma symptom and severity while some report that obesity does not have a significant influence on asthma severity and control (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Higher BMI also led to lower scores on the Asthma Quality of Life Questionnaire 31 . Other studies also study showed that normal-weight had a better asthma control versus obese and overweight patients 32,33 . Similarly, the drug response to asthma medications also vary by the BMI.…”
Section: Obesity and Asthma Managementmentioning
confidence: 91%